Decellularized tissues as platforms for in vitro modeling of healthy and diseased tissues. (15th July 2020) - McCrary, Michaela W.; Bousalis, Deanna; Mobini, Sahba; Song, Young Hye; Schmidt, Christine E.
Abstract: Biomedical engineers are at the forefront of developing novel treatments to improve human health, however, many products fail to translate to clinical implementation. In vivo pre-clinical animal models, although the current best approximation of complex disease conditions, are limited by reproducibility, ethical concerns, and poor accurate prediction of human response. Hence, there is a need to develop physiologically relevant, low cost, scalable, and reproducible in vitro platforms to provide reliable means for testing drugs, biomaterials, and tissue engineered products for successful clinical translation. One emerging approach of developing physiologically relevant in vitro models utilizes decellularized tissues/organs as biomaterial platforms for 2D and 3D models of healthy and diseased tissue. Decellularization is a process that removes cellular content and produces tissue-specific extracellular matrix scaffolds that can more accurately recapitulate an organ/tissue's native microenvironment compared to other natural or synthetic materials. Decellularized tissues hold enormous potential for in vitro modeling of various disease phenotypes and tissue responses to drugs or external conditions such as aging, toxin exposure, or even implantation. In this review, we highlight the need for in vitro models, the advantages and limitations of implementing decellularized tissues, and considerations of the decellularization process. We discuss current research efforts towards applying decellularized tissues as platforms to generate in vitro models of healthy and diseased tissues, and where we foresee the field progressing. A variety of organs/tissues are discussed, including brain, heart, kidney, large intestine, liver, lung, skeletal muscle, skin, and tongue. Statement of Significance: Many biomedical products fail to reach clinical translation due to animal model limitations. Development of physiologically relevant in vitro models can provide a more economic, scalable, and reproducible means of testing drugs/therapeutics for successful clinical translation. The use of decellularized tissues as platforms for in vitro models holds promise, as these scaffolds can effectively replicate native tissue complexity, but is not widely explored. This review discusses the need for in vitro models, the promise of decellularized tissues as biomaterial substrates, and the current research applying decellularized tissues towards the creation of in vitro models. Further, this review provides insights into the current limitations and future of such in vitro models. Graphical abstract: Image, graphical abstract